2017
DOI: 10.1007/s13181-017-0616-6
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Severe Rhabdomyolysis Following Monensin Ingestion

Abstract: Monensin is a veterinary medication not approved for human use by the US Food and Drug Administration. Though poorly studied in humans, this case demonstrates the severe harm that may occur following ingestion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…However, these mechanisms are not only efficient against coccidians, but also can act against mammalian cells, primarily on cardiac and peripheral muscle tissues. Clinical signs of acute rhabdomyolysis, such as muscle weakness and myocardial insufficiency, have been observed in a small number of cases of acute intoxications with monensin and other ionophoric compounds, both in animals and humans, due to accidental ingestion of the pure compounds [9,10,11,12]. The authorization of coccidiostats as feed additives is based on studies that demonstrate the safety of their use in relation to the target species at the highest proposed levels of incorporation in feed or water, and at multiples of that level to establish a margin of safety [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these mechanisms are not only efficient against coccidians, but also can act against mammalian cells, primarily on cardiac and peripheral muscle tissues. Clinical signs of acute rhabdomyolysis, such as muscle weakness and myocardial insufficiency, have been observed in a small number of cases of acute intoxications with monensin and other ionophoric compounds, both in animals and humans, due to accidental ingestion of the pure compounds [9,10,11,12]. The authorization of coccidiostats as feed additives is based on studies that demonstrate the safety of their use in relation to the target species at the highest proposed levels of incorporation in feed or water, and at multiples of that level to establish a margin of safety [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although some acute toxicity cases in humans, due to the ingestion of pure molecules, have been registered [9,10,11,12], major concerns are addressed toward chronic toxicity due to long-term exposure to low coccidiostat levels [7]. The European Food Safety Authority (EFSA) and the Joint FAO/WHO Expert Committee on Food Additives (JECFA) established, on the basis of toxicological data, acceptable daily intakes (ADIs) for all regulatory anticoccidials, ranging from the lowest values for HFG (0.00003 mg/kg body weight/day) to the highest values for NIC (0.2 mg/kg body weight/day) [25].…”
Section: Introductionmentioning
confidence: 99%
“…In India, there were seven human cases of poisoning with maduramicin in porridge by mistake, and four patients unfortunately died after 48 h, with a varying degree of rhabdomyolysis [18]. Other drugs of the same ionophore class, such as monensin and salinomycin, have been reported to cause human intoxication with different levels of rhabdomyolysis in China and other countries [24][25][26]. In addition, extensive use of maduramicin and other ionophores in the livestock production industry increased the environmental release and posed potential risk to ecology safety and public human health in recent years [20,33].…”
Section: Discussionmentioning
confidence: 99%
“…The rhabdomyolysis induced by monensin poisoning is firstly due to increased intracellular sodium concentration, which causes a secondary increase in cytosolic calcium. The accumulation of intracellular calcium may be related to the elevation of calcium influx through the Na þ / Ca 2þ exchange pump, the reduction of calcium outflow to extracellular fluid, and the release of calcium from sarcoplasmic reticula and mitochondria (Blain et al, 2017). The significant increase in intracellular calcium is thought to exert vital roles in monensininduced damage of skeletal muscle and cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that acute monensin poisoning can cause significant rhabdomyolysis and fatal acute renal failure, eventually leading to multiple organ failure and even death (Caldeira et al, 2001; Kouyoumdjian et al, 2001). Another report showed that one case of monensin poisoning also had rhabdomyolysis as the main manifestation but unaccompanied by renal failure, and patients survived after clinical treatment (Blain et al, 2017). Herein, we report two human cases of monensin poisoning with severe rhabdomyolysis and hepatotoxicity caused by oral ingestion.…”
Section: Introductionmentioning
confidence: 99%